The Cognitive Functions in Adults with Chronic Pain: A Comparative Study - Mohammed Shaban Nadar; Zainab Jasem; Fahad S. Manee (Pain Research and Management)
Background. Several studies have reported an association between chronic pain and reduction of cognitive abilities of adults living in Western cultures. No literature could be found on the relationship between chronic pain and cognition among Middle Eastern adults. Objective. To compare four of the most commonly reported cognitive domains [memory, attention, processing speed, and executive functioning] among Middle Eastern adults with and without chronic pain. Methods. This matched group comparative study included 69 community residing and functionally independent Middle Eastern adults. Forty participants had chronic pain and 29 were pain-free. We administered five standardized cognitive assessments that are independent of culture and language to measure variable tasks of memory, attention, processing speed, and executive functioning. The study was conducted in a rehabilitation research setting with a controlled environment. Results. Evidence of decreased cognitive processing was found in patients with chronic pain. The chronic pain participants performed significantly worse than the pain-free participants on the cognitive measures of long-term memory, selective attention, processing speed, and executive functioning. Conclusion. The effect of Middle Eastern culture on the cognitive abilities of patients with chronic pain was negligible. Despite the wide variations between Eastern and Western cultures, the performance of our Middle Eastern participants in this study was consistent with performance of Western adults reported in previous studies.